Los inventarios y su tratamiento en la empresa Mavesa S.A., del cantón Riobamba. - Sani Paredes, Alexander Patricio (2025)
The application of the International Accounting Standard for Inventories (IAS) at a business level is fundamental for the specific case of the company Mavesa S.A., of the Riobamba canton, the present investigation has as objective to propose a system of control and valuation of inventories and its treatment in the company Mavesa S.A., of the Riobamba canton, in order to improve the accounting, costing and control of inventories, as well as to reduce the acquisition costs. The research has a descriptive approach and according to its scope it is a descriptive research in which direct observation and surveys were applied through questions previously validated by the tutors. The results reveal that the company has an incomplete inventory control system, which af fects the accuracy in the availability and movement of goods, worse still, is that internal policies are outdated to manage the procurement, sale, storage and dispatch of products. The research concludes that improving inventory management is crucial to mitigate business deficiencies and ensure informed decision making, given the need to establish internal policies and inventory control systems based on an inventory control and valuation system.